2015
DOI: 10.1080/07391102.2015.1074943
|View full text |Cite
|
Sign up to set email alerts
|

Molecular insight into amyloid oligomer destabilizing mechanism of flavonoid derivative 2-(4′ benzyloxyphenyl)-3-hydroxy-chromen-4-one through docking and molecular dynamics simulations

Abstract: Aggregation of amyloid peptide (Aβ) has been shown to be directly related to progression of Alzheimer's disease (AD). Aβ is neurotoxic and its deposition and aggregation ultimately lead to cell death. In our previous work, we reported flavonoid derivative (compound 1) showing promising result in transgenic AD model of Drosophila. Compound 1 showed prevention of Aβ-induced neurotoxicity and neuroprotective efficacy in Drosophila system. However, mechanism of action of compound 1 and its effect on the amyloid is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 44 publications
2
11
0
Order By: Relevance
“…Several MD simulations have shown that this fibril is very stable under ambient equilibrium conditions, 20,28,45 and can only be dissociated under external forces such as ultrasound, 12 laser excitation, 28 or binding with molecular compounds. 46 The result displayed in Fig. 2(d) shows that when the bubbles reach the maximum size the highest pressure exerted on (A β 17−42 ) 5 is about 3000 bars.…”
Section: Discussionmentioning
confidence: 93%
“…Several MD simulations have shown that this fibril is very stable under ambient equilibrium conditions, 20,28,45 and can only be dissociated under external forces such as ultrasound, 12 laser excitation, 28 or binding with molecular compounds. 46 The result displayed in Fig. 2(d) shows that when the bubbles reach the maximum size the highest pressure exerted on (A β 17−42 ) 5 is about 3000 bars.…”
Section: Discussionmentioning
confidence: 93%
“…The MD simulations were performed using GROMACS (version 5.0.5) with GROMOS96 43a1 force field . GROMOS force field has been widely used to study the structural dynamics of peptides in a number of recent studies 10b,23f,30 . Using GROMOS96, Kumar et al investigated the destabilizing mechanism of flavonoid derivative 2‐(4'benzyloxyphenyl)‐3‐hydroxy‐chromen‐4‐one on the amyloid oligomer structure, 2BEG, using MD simulations of length 35 ns 30a .…”
Section: Methodsmentioning
confidence: 99%
“…GROMOS force field has been widely used to study the structural dynamics of peptides in a number of recent studies 10b,23f,30 . Using GROMOS96, Kumar et al investigated the destabilizing mechanism of flavonoid derivative 2‐(4'benzyloxyphenyl)‐3‐hydroxy‐chromen‐4‐one on the amyloid oligomer structure, 2BEG, using MD simulations of length 35 ns 30a . Autiero et al explored the mechanism of interaction between trehalose‐conjugated beta‐sheet breaker (BSB) peptides and Aβ(1–42) fibrils, 2BEG, by MD simulations of 100 ns using GROMOS96 force field 23f .…”
Section: Methodsmentioning
confidence: 99%
“…The cross-β strands are defined the strands of a β-sheet run vertically to the axis of fibril forming mature fibrils [ 20 ]. As schematically shown in Fig 1 , there are two main strategies to destabilize and/or dissipate the amyloid mature fibrils including; a) changing cross-β strands [ 17 , 21 23 ] mainly based on alteration of Aβ peptides’ quaternary structure ( Fig 1 , pathways 1 and 1' ), and b) focusing on the dissociated β strands from fibrils and converting β-sheet conformations to other secondary structures (changing tertiary and predominantly secondary structures of peptides, pathway 2 ). The disruption of mature fibrils is an effective procedure to decrease the toxicity of amyloid’s plaques at therapeutic mediation in the late phase of AD.…”
Section: Introductionmentioning
confidence: 99%
“…Both experimental and theoretical literatures currently suggest that flavonoids-related compounds inhibit early stage of Aβ aggregation which also disrupt the late stages of the of Alzheimer’s cross-β fibrils, providing the motivation for the present study. The structural feature of oligomeric protofilament state of Aβ17–42 peptides and destabilizing cross oligomeric-β by the interaction with flavonoids (pathways 1 and 1' ) have been extensively studied using MD simulation methods [ 17 , 21 , 23 , 29 ]. Besides, despite of wide studies on Aβ peptides’ fibrillogenesis, the conformational stability and affinity of the fibril Aβ17–42 peptide in the case of interaction with excipients remains unclear.…”
Section: Introductionmentioning
confidence: 99%